Patientologien nyfortolket - Schneider-Kamp, Anna; Nielsen, Helle Lykke; Isaksen, Jytte; Geyer, Klaus; Lindell, Johanna; Sodemann, Morten (K&K - Kultur og Klasse, 2021)
Patientology traditionally signifies the scientific study of the patients through medical sociological and anthropological perspectives. The last decades have witnessed notable changes in the understanding of what it means to be a patient and what role patients play in healthcare processes, with the rise of concepts such as patient-centered care, patient empowerment, and patient participation. This article develops a reconceptualization of patientology, proposes a model hereof, and exemplifies its use through the application to an illustrative case. Our reconceptualization of patientology considers the patient as the central actor in a network of healthcare actors. Being a patient requires health capital that is comprised of health-relevant aspects of Bourdieusian forms of capitals: economic, social, and cultural capital. The patient role is constructed through the patient’s interaction with a range of healthcare actors such as health professionals, relatives, and other patients. The proposed model allows for understanding health inequalities as based on differences in (cultural) health capital, opening up new avenues of investigating and ameliorating patients’ challenges in health interactions. The model allows for a fresh take on the reciprocity of Parsons social sick role, allowing to clarify both how patients can contribute to their own health and healthcare and where and how health professionals ought to meet their patients.